Beyond the itch: the complex interplay of immune, neurological, and psychological factors in chronic urticaria - Shurui Yang; Li Chen; Haiming Zhang; Yanjuan Song; Wenyan Wang; Zhengbo Hu; Siyu Wang; Liuyang Huang; Yayuan Wang; Song Wu; Rui Chen; Fengxia Liang (Journal of Neuroinflammation)
Abstract Chronic urticaria (CU) arises from a multifaceted interplay of immunological, neurological, and psychological components. Immune dysregulation, mediated through both immunoglobulin E (IgE)-dependent and IgE-independent pathways, plays a pivotal role in CU pathogenesis, involving key effector cells such as mast cells (MCs), basophils, and eosinophils. This dysregulation culminates in the release of histamine, prostaglandins, and other mediators, which precipitate pruritus. The chronicity of the disease leads to sustained pruritic symptoms, contributing to both central and peripheral sensitization. The excitation of the itch circuit is augmented, leading to the release of neurotransmitters and neuropeptides, which subsequently interact with immune cells. Psychological factors such as depression, anxiety, and stress exacerbate CU symptoms and diminish quality of life. These factors disrupt the hypothalamic-pituitary-adrenal (HPA) axis and the autonomic nervous system (ANS). Furthermore, the act of scratching activates the reward circuit, resulting in the manifestation of the itch-scratching cycle. Current treatments, such as antihistamines, omalizumab, and cyclosporine, demonstrate variable efficacy and are often associated with adverse effects. A holistic approach addressing both psychological and physiological aspects is advocated. This review highlights the critical importance of understanding neuroimmune interactions and the influence of psychosomatic factors in CU. It aims to enhance diagnostic and therapeutic strategies by integrating psychological, neurological, and immunological perspectives.